Forging plant OJSC «MAZ». 70 years of history and prospects of development - P. S. Gurchenko; V. I. Starovoitov; V. I. Strazhevich (Литьë и металлургия)
The data on the history of the formation and development of forging and blank production, reorganization of departments and sections of the forging plant at OJSC «MAZ» are given. The technologies of shaping and forging used in press – forging and thermal equipment are described. The main measures to ensure the production volume and quality of forgings are listed, improvement of working conditions and environmental conditions at the plant are shown. A brief description of the means of mechanization and automation of technological processes of forgings manufacturing with the use of induction heating created at MAZ is given. Prospects of development of blank production are considered.